Increasing identity and community awareness in Medan City about victim rights of sexual violence - Sirait, Ningrum Natasya; Rosmalinda; Ikhsan, Edy; Siregar, Mahmul; Agusmidah (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Indonesia currently has Law Number 11 of 2012 concerning the Criminal Justice System for Children (UU-SPPA) to provide protection for children who need special protection such as child offenders, victims and witnesses. In fact, the implementation of the UU-SPPA actually only focuses on children as perpetrators. This not only shows that justice for children is still not upright especially for children who are victims of sexual violence. This is evident from the findings of a study conducted in 2019 entitled "The Effectiveness of the Convention on the Rights of the Child Victims of Sexual Violence". This study found that although Indonesia already has 2 government regulations governing the fulfillment of victims of sexual violence in the form of compensation and or restitution, none of the decisions of the Medan District Court and Lubuk Pakam contain the rights of victims. The decisions of the Medan District Court and Lubuk Pakam throughout 2018 were oriented towards providing penalties for the perpetrators. The two Government Regulations which are guidelines for implementing the Law are (a) Government Regulation of the Republic of Indonesia Number 7 of 2018 concerning Provision of Compensation, Restitution and Assistance to Witnesses and Victims; and (b) Government Regulation of the Republic of Indonesia Number 43 Year 2017 Concerning Implementation of Restitution for Children Who Are Victims of Criminal Acts. These two Government Regulations are the basic ingredients for the implementation of the 2019 Mandatory Servant Lecturer service dedication. This situation is the basis of community service in two districts namely Medan Baru and Medan Sunggal. Law Enforcement Officials (APH) in this case the police and the community not only obtain new information about victims' rights but also increase their awareness to guarantee the rights of children victims of sexual violence are requested in legal proceedings for perpetrators. Furthermore, the Police and the community hope that the information on these two Government Regulations can be continued both by the Regional Government Organization (OPD) and other institutions such as the Civil Society Organization (CSO) in Medan.